Effects of Methylprednisolone on Femoral Bone Marrow: Age-Dependent Susceptibility. Issue 5 (September 2013) - Chan, Wing P.; Kuo, Tzong-Fu; Lin, Yun-Ho; Chen, Chia-Chun; Yang, Shu-Ru; Huang, Sydney; Jiang, Ching-Chuan
Purpose: We aimed to test our primary hypothesis that the effects of methylprednisolone on bone marrow in chickens are age-sensitive and increase with prolonged treatment and our secondary hypothesis that the effects of methylprednisolone on bone marrow can have individual effects. Methods: Sixteen control (group A) and 29 methylprednisolone-treated (group B) chickens were categorised by age: pubertal chicks (subgroups A1, B1), young hens (A2, B2), and adult hens (A3, B3). Histologic evaluation 12 to 50 weeks after the start of methylprednisolone treatment included fat cell proliferation, trabecular bone loss, necrosis of bone and marrow, and new bone formation in the femoral head, neck, and intertrochanteric area. Results: There were significant differences between groups A1 and B1 in new bone formation in the femoral neck (P = 0.048) and fat cell proliferation in the femoral head (P = 0.008) and neck (P = 0.048). New bone formation in the femoral head was also significantly different (P = 0.023) between groups A2 and B2. No differences were noted between groups A3 and B3 (all P>0.05). Necrosis of bone and marrow was observed in four control and three methylprednisolone-treated chickens (P>0.05). Significant new bone formation and fat cell proliferation in pubertal and young chickens occurred 12 to 19 weeks after administration of high-dose methylprednisolone. Conclusions: Younger animals may be more susceptible to methylprednisolone, and responses to methylprednisolone in femoral marrow may vary among individuals.